The Old and New Town: The Future of Warsaw Legendary Characters - Niewieczerzał, Marta (Literatura Ludowa. Journal of Folklore and Popular Culture, 2019)
This article presents a comparison of depictions of selected characters from traditional urban legends and their postmodern versions in contemporary Polish children's and YA literature. The analysis herein focuses on Warsaw Legends and characters related to them (the Golden Duck, Wars and Sawa, Basilisk and others). The article outlines problems associated with the future as a category concerning the individual, i.e. specific characters from the Warsaw Legends: how do they change and mature? What kind of future awaits them in the new reality? The article also examines selected narrative strategies aimed at modifying the original in the analyzed texts.